100 yards of glory : the greatest moments in NFL history - Garner, Joe (Houghton Mifflin Harcourt, 2011)
"The Immaculate Reception. The Ice Bowl. The Music City Miracle. The Catch. For nearly a century, the National Football League has provided fans with pulse-pounding moments on the gridiron. From the great dynasties to the improbable catches, the legendary coaches to the heroic QBs, the most incredible comebacks to the most notorious flubs, 100 Yards of Glory relives the most unforgettable moments in the game.